2019
DOI: 10.4081/cp.2019.1096
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Hemopericardium after Initiation of Rivaroxaban: Implications and Potential Mechanisms

Abstract: Direct oral anticoagulants have become increasingly used for atrial fibrillation and venothromboembolic disease. Thus far, there have been a few published cases of pericardial effusion associated with rivaroxban. However, there has been little published regarding the effects of concurrent medications and their effect on the cytochrome enzyme systems involved in rivaroxaban metabolism. We present a case of a 76-year-old female who develops a spontaneous haemopericardium after initiating rivaroxaban. After thoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Atia R et al reported two cases of spontaneous choroidal hemorrhage in patients taking rivaroxaban and dabigatran [32]. Hemorrhagic cardiac tamponade and spontaneous hemopericardium have been reported in patients receiving DOACs [33][34][35]. Jun et al reported three cases of spontaneous vitreous hemorrhage in patients taking rivaroxaban for atrial fibrillation.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Atia R et al reported two cases of spontaneous choroidal hemorrhage in patients taking rivaroxaban and dabigatran [32]. Hemorrhagic cardiac tamponade and spontaneous hemopericardium have been reported in patients receiving DOACs [33][34][35]. Jun et al reported three cases of spontaneous vitreous hemorrhage in patients taking rivaroxaban for atrial fibrillation.…”
Section: Epidemiologymentioning
confidence: 99%
“…Bleeding complications from direct oral anticoagulant use[10,20,[22][23][24][25][26][27][30][31][32][33][34][35][37][38][39]42].…”
mentioning
confidence: 99%
“…Decreased expression of P-gp [25][26][27][28] May necessitate decrease in dose/frequency of medications used to treat pericarditis and/or disorders exacerbated by thyroid disease: 20,22 -Increased risk of exacerbating cardiovascular events in patients with underlying CAD, HTN, and/or HF -Some NSAIDs may interfere with thyroid function tests Colchicine 12,23,29 -Monitor CK and hs-CRP as part of surrogate laboratory response to treatment -Increased risk for myopathy; synergistic drug-disease interaction with colchicine and hypothyroidism Glucocorticoids 14,30 Increased risk for osteoporosis; synergistic drug-disease interaction with glucocorticoids and hypothyroidism Anticoagulation [44][45][46][47][48] -Hemopericardium in setting of pericardial effusion and anticoagulation -Hypothyroidism may potentiate the effects of anticoagulants Hyperthyroidism Increased expression of P-gp [25][26][27][28] May necessitate increase in dose/frequency of medications used to treat pericarditis and/or disorders exacerbated by thyroid disease: 23,29,41 -Increased risk for diarrhea because of synergistic drug-disease interaction -Monitor SCr, LFTs, and CBC with differential; synergistic drug-drug interaction with PTU, MTI, and colchicine NSAIDs 22,40 -Increased risk of exacerbating cardiovascular events in patients with underlying HTN and/ or HF -Use with caution in patients receiving anticoagulation for atrial fibrillation or atrial flutter -Competes with thyroxine for albumin-binding site; may exacerbate thyrotoxicosis Atrial fibrillation Rate control 24,29 Several rate controlling agents inhibit P-gp and can increase plasma concentration of colchicine: 24,29 Several antidysrhythmic agents inhibit P-gp and can increase plasma concentration of colchicine:…”
Section: Hypothyroidismmentioning
confidence: 99%
“…• Dronedarone • Amiodarone • Propafenone Anticoagulation [44][45][46][47][48] -Hemopericardium secondary to potentiated anticoagulant effect -Hyperthyroidism may diminish the effects of anticoagulants Abbreviations: CAD, coronary artery disease; CBC, complete blood count; CK, creatine kinase; HF, heart failure; hs-CRP, high-sensitivity C-reactive protein; HTN, hypertension; LFTs, liver function tests; MTI, methimazole; NSAID, nonsteroidal anti-inflammatory drug; P-gp, P-glycoprotein; PTU, propylthiouracil; SCr, serum creatinine.…”
Section: Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation